A novel splicing mutation identified in a DMD patient: a case report - Wen, Yuting; Yang, Luo; Shen, Gan; Dai, Siyu; Wang, Jing; Wang, Xiang (Frontiers in Pediatrics, 2023)
Duchenne muscular dystrophy (DMD, ORPHA:98896) is a lethal X-linked recessive disease that manifests as progressive muscular weakness and wasting. Mutations in the dystrophy gene (DMD) are the main cause of Duchenne muscular dystrophy.This study aims to determine novel mutations of DMD and help preimplantation genetic diagnosis (PGD) for family planning. Here present a four-year-old Chinses boy with DMD, whole-exome sequencing (WES) was performed to identify the molecular basis of the disease. It was confirmed that the boy carried a novel hemizygous mutation of NC_000023.11(NM_004006.3): c.5912_5922+19delinsATGTATG in DMD which inherited from his mother. This led to the aberrant splicing of DMD which demonstrated by a minigene splicing assay and further resulted in the impairment of the dystrophy protein.Our study discovered a novel splicing mutation of DMD in a DMD patient, which expands the variant spectrum of this gene and provide precise genetic diagnosis of DMD for timely therapy. Meanwhile, this finding will supply valuable information for preimplantation genetic diagnosis.